Cytochromes P450 reconstituted with NADPH: P450 reductase mimic the activating and detoxicating metabolism of the anticancer drug ellipticine in microsomes - Kotrbová, Vera; Aimová, Dagmar; Brezinová, Anna; Janouchová, Katerina; Poljaková, Jitka; Frei, Eva; Stiborová, Marie (Neuro endocrinology letters, 2006)
OBJECTIVES: Ellipticine is a potent antineoplastic agent exhibiting multiple action mechanisms. Recently, we found that after cytochrome P450 (CYP)-mediated oxidation ellipticine forms covalent DNA adducts. Ellipticine oxidation by isolated CYP and its binding to DNA is the target of this study. METHODS: High performance liquid chromatography (HPLC) was employed for separation and characterization of ellipticine metabolites generated by CYPs. The (32)P-postlabeling technique was utilized to determine ellipticine-DNA adducts. RESULTS: Purified CYP enzymes reconstituted with NADPH:CYP reductase oxidized ellipticine to up to five metabolites, 7-hydroxy-, 9-hydroxy-, 12-hydroxy-, 13-hydroxyellipticine and ellipticine N(2)-oxide. However, only CYP1A1 was capable to form all metabolites. Using the reconstituted enzymatic system, we demonstrated that the detoxication ellipticine metabolites, 7-hydroxyellipticine and 9-hydroxyellipticine, are mainly generated by CYP1A1 and 1A2, while those responsible for DNA binding, 13-hydroxy-, 12-hydroxyellipticine and ellipticine N(2)-oxide, by CYP3A1 and 2C3. Likewise, the most efficient CYPs forming DNA adducts from ellipticine were CYP3A1 and 2C3. CONCLUSIONS: The results showed that the system of purified CYPs reconstituted with NADPH: CYP reductase proved for ellipticine oxidation provide a true reflection of the situation in the microsomal membrane.
Keywords: Animals; NADPH-Ferrihemoprotein Reductase; biologické modely; Rabbits; Metabolic Detoxication, Phase I; NADPH-cytochrom c-reduktasa; Models, Biological; adukty DNA; Antineoplastic Agents; protinádorové látky; jaterní mikrozomy; I. fáze biotransformace; Ellipticines; DNA Adducts; systém (enzymů) cytochromů P-450; Microsomes, Liver; krysa rodu Rattus; NADP; králíci; zvířata; elipticiny; Rats; Cytochrome P-450 Enzyme System